INTERTEXTUAL ELEMENTS IN POLITICAL TEXTS AND THEIR COMMUNICATIVE SIGNIFICANCE (Scientific journal of the Fergana State University, 2026)
This article analyzes intertextual elements in political texts and their communicative significance based on linguopragmatic, cognitive, and discursive approaches. The results of the study showed the important role of intertextual elements in ensuring legitimacy, trust, and ideological coherence in political speech. Statistical analysis revealed that intertextual references, especially citations and historical allusions, are most actively used in political texts. Intertextuality manifests itself in political communication as a means of effectiveness, solidarity, and the formation of national identity.